2023
DOI: 10.13057/biodiv/d240549
|View full text |Cite
|
Sign up to set email alerts
|

Genetic diversity of the genus Citrus in Tomini Bay coastal areas, Indonesia based on morphological characters

Abstract: Abstract. Kandowangko NY, Febriyanti. 2023. Genetic diversity of the genus Citrus in Tomini Bay coastal areas, Indonesia based on morphological characters. BIodiversitas 24: 2938-2952. Citrus plants are one of the fruit plants that are widely consumed by the community, both for food, health, and customs. The existence of Citrus plants in the coastal area of Tomini Bay only grows wild and has not been cultivated intensively. Lack of information on the diversity of citrus and the use of Citrus plants that are no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
1
2
0
Order By: Relevance
“…That research found the value of diversity index was 0.8103, that was considered low. It was also recorded a similarity coefficient of 64.3% in the group consisted of seven citruses on the dendrogram, and formed two primary groups that were classified into smaller categories at the species diversity level (Kandowangko and Febriyanti 2023). Morphological characterization of the same citrus variation in this study is relatively comparable with other locations in Indonesia (Murtando et al 2016;Sofiyanti et al 2022).…”
Section: Phenetic Analysissupporting
confidence: 74%
See 2 more Smart Citations
“…That research found the value of diversity index was 0.8103, that was considered low. It was also recorded a similarity coefficient of 64.3% in the group consisted of seven citruses on the dendrogram, and formed two primary groups that were classified into smaller categories at the species diversity level (Kandowangko and Febriyanti 2023). Morphological characterization of the same citrus variation in this study is relatively comparable with other locations in Indonesia (Murtando et al 2016;Sofiyanti et al 2022).…”
Section: Phenetic Analysissupporting
confidence: 74%
“…Genetic differences occur not only between species; even within one species, there is gene diversity. With the diversity of genes, the characteristics within one species are diverse and varied or are referred to as varieties, even to the point of accession (Kandowangko and Febriyanti 2023).…”
Section: Morphological Characters Of Leafmentioning
confidence: 99%
See 1 more Smart Citation
“…The study of morphological characteristics of Rutaceae accessions revealed that length of petiole relative to length of leaf lamina, leaf apex, branch angle and density of branches are the main factor in differentiating the accessions in PC's. These differentiating characters were also con rmed by Kandowangko and Febriyanti (2023) under the genus Citrus.…”
Section: Discussionmentioning
confidence: 64%